Position of the Presidential Staff Office in the Indonesian State Administration System - Mella Rosdiyana; Mesraini Mesraini (STAATSRECHT: Indonesian Constitutional Law Journal, 2021)
The primary concern of this study is the position of the Presidential Staff Office in the Indonesian constitutional system following the publication of Presidential Regulation Number 26 of 2015 pertaining to the Presidential Staff Office. Articles 1 through 4 of Presidential Regulation Number 26 of 2015 describe the mission of the Presidential Staff Office as an increase in the seamless supervision of national priority projects and the organizers of presidential political communication, in addition to the management of strategic concerns. This study employs normative legal scholarship. The findings of this study indicate that the position of the Presidential Staff Office (KSP) is a category of state organs that are auxiliary or supporting (auxiliary organ state) from the implementation instruments of the main state institutions (main organ state/constitutional organ) with a hierarchical structure of group/third tier state institutions where resources the authority of the regulator/establishment based on the law or a Presidential Decree.